Analisis Persepsi Mahasiswa Akuntansi Mengenai Faktor – Faktor Yang Mempengaruhi Pemilihan Karir Sebagai Akuntan Publik Dan Non Akuntan Publik (Studi Kasus Pada Mahasiswa Akuntansi Universitas Kristen Petra Surabaya) - Frederick Wongsodihardjo; Raynald Iskandar; Yulius Jogi Christiawan (Business Accounting Review, 2020)
This study aimed to identify and analyze the factors that influence accounting students in choosing their careers as public accountants or non-public accountants. The factors used as variables are financial rewards, professional training, professional recognition, social values, work environments, labor market considerations, and personality. This research is a survey research that uses primary data through a questionnaire distribution. The population in this study were students majoring in accounting at Petra Christian University Surabaya in 2021. The sample selection was made by using a simple random sampling technique, and the resulting sample of 436 respondents consisting of 178 business accounting students, 237 tax accounting students, and 21 International business Accounting (IBAcc) students. Data analysis of this research using logistic regression method with the help of a computer program, namely SPSS (Statistical Program for Social Science). The result shows that the factors of work environment and labor market considerations have a significant effect on student career choices as a public accountants and non-public accountants. While the factors of financial rewards, professional training, professional recognition, social values, and personality did not significantly influence the career choices of students as public accountants and non-public accountants.